2022
DOI: 10.1001/jamanetworkopen.2022.32842
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Fractional Flow Reserve After Coronary Stenting

Abstract: ImportanceFractional flow reserve (FFR) after percutaneous coronary intervention (PCI) is generally considered to reflect residual disease. Yet the clinical relevance of post-PCI FFR after drug-eluting stent (DES) implantation remains unclear.ObjectiveTo evaluate the clinical relevance of post-PCI FFR measurement after DES implantation.Data SourcesMEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were searched for relevant published articles from inception to June 18, 2022.Study Selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 64 publications
1
40
1
Order By: Relevance
“…Although clinical outcomes between IVUS and FFR groups were not significantly different according to the prespecified optimization criteria in this study, high-risk revascularized vessels can be defined using the optimal cutoff of post-PCI FFR, MSA, and plaque burden at stent edge, which were associated with a higher risk of TVF than low-risk revascularized vessels. This finding aligns with prior publications that reported the prognostic value of residual ischemia, or IVUS-defined post-PCI plaque burden or stent underexpansion . It should be noted that there was no statistically significant association of continuous FFR and IVUS parameters with TVF did in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although clinical outcomes between IVUS and FFR groups were not significantly different according to the prespecified optimization criteria in this study, high-risk revascularized vessels can be defined using the optimal cutoff of post-PCI FFR, MSA, and plaque burden at stent edge, which were associated with a higher risk of TVF than low-risk revascularized vessels. This finding aligns with prior publications that reported the prognostic value of residual ischemia, or IVUS-defined post-PCI plaque burden or stent underexpansion . It should be noted that there was no statistically significant association of continuous FFR and IVUS parameters with TVF did in this study.…”
Section: Discussionsupporting
confidence: 92%
“…While intravascular imaging is recommended for planning and optimization of PCI, poststent physiological assessment can also independently estimate risk of adverse clinical events after stent implantation . Nonetheless, head-to-head comparison of clinical outcomes between physiology- and imaging-based PCI optimization has rarely been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that FFR values measured after PCI could predict the long-term outcome of patients [25]. Systematic reviews and metaanalysis had also reached similar conclusions [10,26]. In recent years, studies had shown that QFR could also predict post-PCI VOCE [1,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 83%
“…Tis method should be feasible. Tis is also the case with other metaanalysis, such as the meta-analysis published by Hwang [26] in JAMA in 2022. Hence, the results of this study should be considered exploratory.…”
Section: Limitationsmentioning
confidence: 84%
“…23 This is based on the fact that not all PCIs were necessarily physiologically optimized, despite physiology-guided and angiographically successful PCI, and that clinical outcomes differed significantly according to post-PCI physiological optimization. 24 Meanwhile, there has been an attempt to use IVUS as a treatment decision-making tool. In a previous study by Nam et al, IVUS-guided treatment decision-making resulted in higher rates of revascularization than FFR-guided treatment decision-making in 167 patients with intermediate coronary artery stenosis; however, there was no significant difference in major adverse cardiac event rates between the 2 groups at 1 year.…”
Section: Discussionmentioning
confidence: 99%